Molecular evidence of hybridization between pig and human Ascaris indicates an interbred species complex infecting humans - Easton, Alice; Gao, Shenghan; Lawton, Scott P; Bennuru, Sasisekhar; Khan, Asis; Dahlstrom, Eric; Oliveira, Rita G; Kepha, Stella; Porcella, Stephen F; Webster, Joanne; Anderson, Roy; Grigg, Michael E; et al. (eLife, 2020)
Human ascariasis is a major neglected tropical disease caused by the nematode Ascaris lumbricoides . We report a 296 megabase (Mb) reference-quality genome comprised of 17,902 protein-coding genes derived from a single, representative Ascaris worm. An additional 68 worms were collected from 60 human hosts in Kenyan villages where pig husbandry is rare. Notably, the majority of these worms (63/68) possessed mitochondrial genomes that clustered closer to the pig parasite Ascaris suum than to A. lumbricoides . Comparative phylogenomic analyses identified over 11 million nuclear-encoded SNPs but just two distinct genetic types that had recombined across the genomes analyzed. The nuclear genomes had extensive heterozygosity, and all samples existed as genetic mosaics with either A. suum -like or A. lumbricoides -like inheritance patterns supporting a highly interbred Ascaris species genetic complex. As no barriers appear to exist for anthroponotic transmission of these ‘hybrid’ worms, a one-health approach to control the spread of human ascariasis will be necessary.